2022
DOI: 10.3390/cancers14164012
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Predictive Models of Response to Cytotoxic Chemotherapy Alone or Combined to Targeted Therapy for Metastatic Colorectal Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: Tailored treatments for metastatic colorectal cancer (mCRC) have not yet completely evolved due to the variety in response to drugs. Therefore, artificial intelligence has been recently used to develop prognostic and predictive models of treatment response (either activity/efficacy or toxicity) to aid in clinical decision making. In this systematic review, we have examined the ability of learning methods to predict response to chemotherapy alone or combined with targeted therapy in mCRC patients by targeting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 141 publications
(354 reference statements)
1
5
0
Order By: Relevance
“…Additionally, missing data, and handling of missing data, were reported rarely. This was also observed in other systematic reviews of predictive models [41] , [42] . Finally, there was some heterogeneity across the predictors used in the identified models, even where the models aimed to predict the same outcome [29] , [31] , [35] .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, missing data, and handling of missing data, were reported rarely. This was also observed in other systematic reviews of predictive models [41] , [42] . Finally, there was some heterogeneity across the predictors used in the identified models, even where the models aimed to predict the same outcome [29] , [31] , [35] .…”
Section: Discussionsupporting
confidence: 84%
“…An additional two studies validated existing predictive models externally. External validation is critical to ensuring model generalisability and is an important step before model application in clinical settings [41] . The lack of external validation may be in part due to the novelty of predictive models in cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…Russo et al used AI-based prediction model to analyze the patients who may have drug resistance before and after treatment. They achieved a sound effect (average AUC = 0.90) in the classification and targeted precision treatment ( 154 ). Interestingly, with the help of artificial algorithms, Hu et al studied the competitive endogenous RNA (ceRNA) network about lncRNA and proposed 144 core genes for the first time, which could be used as target drugs for the treatment of CRC ( 155 ).…”
Section: The Application Of Ai In Crc Treatmentmentioning
confidence: 99%
“…In a more recent systematic review and meta-analysis, Russo et al. analyzed the use of AI in predictive models of the response to cytotoxic chemotherapy alone or combined with targeted therapy in patients with metastatic CRC in 26 original articles ( 25 ). In their meta-analysis, which included ten articles, they found that the overall weighted means of the AUC were 0.90 in the training sets and 0.83 in the validation sets.…”
Section: Therapeutics: Predicting Response To Therapymentioning
confidence: 99%